Regulation of biotransformation systems and ABC transporters by Benznidazole in HepG2 cells: involvement of Pregnane X-Receptor - Rigalli, Juan Pablo (2012)
Background: Benznidazole (BZL) is the only antichagasic drug available in most endemic countries. Its effect on the expression and activity of drug-metabolizing and transporter proteins has not been studied yet. Methodology/Principal Findings: Expression and activity of P-glycoprotein (P-gp), Multidrug resistance-associated protein 2 (MRP2), Cytochrome P450 3A4 (CYP3A4), and Glutathione S-transferase (GST) were evaluated in HepG2 cells after treatment with BZL. Expression was estimated by immunoblotting and real time PCR. P-gp and MRP2 activities were estimated using model substrates rhodamine 123 and dinitrophenyl-S-glutathione (DNP-SG), respectively. CYP3A4 and GST activities were evaluated through their abilities to convert proluciferin into luciferin and 1-chloro-2,4-dinitrobenzene into DNP-SG, respectively. BZL (200 µM) increased the expression (protein and mRNA) of P-gp, MRP2, CYP3A4, and GSTπ class. A concomitant enhancement of activity was observed for all these proteins, except for CYP3A4, which exhibited a decreased activity. To elucidate if pregnane X receptor (PXR) mediates BZL response, its expression was knocked down with a specific siRNA. In this condition, the effect of BZL on P-gp, MRP2, CYP3A4, and GSTπ protein up-regulation was completely abolished. Consistent with this, BZL was able to activate PXR, as detected by reporter gene assay. Additional studies, using transporter inhibitors and P-gp-knock down cells, demonstrated that P-gp is involved in BZL extrusion. Pre-treatment of HepG2 cells with BZL increased its own efflux, as a consequence of P-gp up-regulation. Conclusions/Significance: Modifications in the activity of biotransformation and transport systems by BZL may alter the pharmacokinetics and efficiency of drugs that are substrates of these systems, including BZL itself.